Stability of PEDOT:PSS‐Coated Gold Electrodes in Cell Culture Conditions. Issue 3 (25th October 2019) - Dijk, Gerwin; Rutz, Alexandra L.; Malliaras, George G.
Abstract: Poly(3, 4‐ethylenedioxythiophene) doped with polystyrene sulfonate (PEDOT:PSS) is widely used as a coating on microelectrode arrays in order to reduce impedance for both in vitro and in vivo electrophysiology. In many applications, electrode performance of months to years is desired; yet, there are few studies to date that examine the long‐term stability of conducting polymers and their devices. Here, the stability of PEDOT:PSS microelectrodes is examined over a period of four months in cell culture media enriched with fetal bovine serum. The electrochemical impedance remains constant for most electrodes throughout the study, and only small changes in the structure of functional electrodes are observed. The results demonstrate that PEDOT:PSS electrodes show adequate stability for a variety of in vitro electrophysiology applications in toxicology, drug development, tissue engineering, and fundamental studies of electrically active cells and tissues. Abstract : The long‐term performance of PEDOT:PSS coated microelectrodes is studied for 4 months in cell culture media at 37 °C. The electrochemical impedance remains constant for most electrodes, and only small changes in the structure of the electrodes are observed. The stability of these electrodes makes them viable for many in vitro electrophysiology applications.